Aromatic polymer compositions for use in camera modules
By using a combination of thermal etropic liquid crystal polymer and tribological formula in the camera module, the problem of surface wear of liquid crystal polymer is solved, achieving low friction, low wear and high mechanical properties.
Patent Information
- Application Number
- JP2023125237
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-17
- Filing Date
- 2023-08-01
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2038-11-28
AI Technical Summary
Existing liquid crystal polymers are prone to surface wear in camera modules, resulting in reduced performance and poor appearance.
A polymer composition is used, which comprises a thermal etropic liquid crystal polymer and a tribological formulation containing a fluoride additive and a polymer siloxane. The weight ratio of this formulation is 0.5 to 12 times that of fluoride additives and siloxanes.
The friction coefficient on the polymer surface is significantly reduced, the surface wear is reduced, the performance and appearance quality of the camera module are improved, while maintaining good mechanical properties.
Smart Images

Figure 0007659598000008 
Figure 0007659598000009 
Figure 0007659598000001
Abstract
Description
[Technical field]
[0001]
[0001] This application claims priority to U.S. Patent Application Nos. 62 / 594,603 (filed December 5, 2017) and 62 / 746,757 (filed October 17, 2018), which are incorporated by reference in their entireties. [Background technology]
[0002] Camera modules (or components) are often used in mobile phones, laptop computers, digital cameras, digital video cameras, etc. Examples include compact camera modules including a carrier mounted on a base, Examples include digital camera shutter modules, components of digital cameras, cameras in game consoles, medical cameras, security cameras, etc. Such camera modules have become more complex and now tend to include many moving parts. For example, in some cases, two compact camera module assemblies can be mounted in a single module to improve image quality (a "dual camera" module). In other cases, an array of compact camera modules can be used. Regardless of the specific design, liquid crystal polymers are often used during manufacturing due to their highly oriented crystalline structure, which allows the polymers to be easily molded into very small and intricate parts. Unfortunately, however, the highly oriented structure also makes liquid crystal polymers susceptible to wear; that is, one or more skin layers of the polymer tend to peel off from the part during use, which can result in inferior appearance and / or performance. Summary of the Invention
[0003]
[0003] Therefore, a need exists for polymer compositions that can be easily used in camera modules.
[0004] According to one embodiment of the present invention, a polymer composition is disclosed that includes at least one aromatic polymer (e.g., a thermotropic liquid crystal polymer) and a tribological formulation in an amount of about 1 to about 20 parts by weight per 100 parts by weight of the aromatic polymer. The tribological formulation includes a fluorinated additive and a siloxane polymer having a weight average molecular weight of about 100,000 grams / mole or more. The weight ratio of the fluorinated additive to the siloxane polymer is about 0.5 to about 12.
[0004]
[0005] According to yet another embodiment of the present invention, a camera module is disclosed that includes a base on which a support assembly is mounted. The base, the support assembly, or both include a molded part. The molded part includes a polymer composition that includes at least one thermotropic liquid crystalline polymer and a tribological formulation. The polymer composition exhibits a dynamic coefficient of friction of about 0.4 or less as determined according to VDA 230-206:2007.
[0005]
[0006] Other features and aspects of the invention are set forth in more detail below.
[0007] A full and enabling disclosure of the present invention, including the best mode thereof to one of ordinary skill in the art, is set forth more particularly in the remainder of the specification, including reference to the accompanying drawings, in which: [Brief description of the drawings]
[0006] [Figure 1]
[0008] FIG. 1 is a perspective view of a compact camera module (CCM) that can be formed in accordance with one embodiment of the present invention. [Diagram 2] FIG. 2 is a front view of a compact camera module (CCM) that can be formed in accordance with one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007]
[0009] Those skilled in the art will appreciate that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.
[0010] Generally speaking, the present invention relates to a polymer composition comprising an aromatic polymer in combination with a tribological formulation. The inventors have found that by selectively controlling the nature of these components and their relative concentrations, the resulting polymer composition can achieve a low degree of surface friction that minimizes the degree to which the skin layer delaminates during use of a part containing the composition (e.g., in a camera module). For example, the polymer composition can exhibit a dynamic coefficient of friction of about 1.0 or less, in some embodiments about 0.4 or less, in some embodiments about 0.35 or less, and in some embodiments from about 0.1 to about 0.3, as determined according to VDA 230-206:2007. Also, the wear depth can be about 500 micrometers or less, in some embodiments about 200 micrometers or less, in some embodiments about 100 micrometers or less, and in some embodiments about 10 to about 70 micrometers, as determined according to VDA 230-206:2007.
[0008]
[0011] It was previously believed that parts with such low friction surfaces also did not have sufficiently good mechanical properties. However, contrary to conventional belief, it has been found that the compositions of the present invention have excellent mechanical properties. For example, the compositions have a friction coefficient of about 20 kJ / m2 measured at 23° C. according to ISO test No. 179-1:2010 (technically equivalent to ASTM D256-10e1). 2 and in some embodiments, from about 25 to about 100 kJ / m 2 In some embodiments, from about 30 to about 80 kJ / m 2 The composition may also exhibit a Charpy unnotched impact strength of about 0.5 kJ / m2, as measured at 23° C. according to ISO Test No. 179-1:2010 (technically equivalent to ASTM D256-10e1). 2 and in some embodiments from about 1 to about 20 kJ / m 2In some embodiments, from about 5 to about 15 kJ / m 2 The composition may exhibit a Charpy notched impact strength of about 20 to about 500 MPa, in some embodiments, about 50 to about 400 MPa, and in some embodiments, about 60 to about 350 MPa; a tensile break strain of about 1% or more, in some embodiments, about 2% to about 15%, and in some embodiments, about 3% to about 10%; and / or a tensile modulus of about 4,000 MPa to about 20,000 MPa, in some embodiments, about 5,000 MPa to about 18,000 MPa, and in some embodiments, about 6,000 MPa to about 12,000 MPa. The tensile properties are measured according to ISO Test No. 527:2012 (technically equivalent to ASTM D638-14). The compositions may also exhibit a flexural strength of from about 20 to about 500 MPa, in some embodiments from about 50 to about 400 MPa, and in some embodiments from about 80 to about 350 MPa, and / or a flexural modulus of from about 4,000 MPa to about 20,000 MPa, in some embodiments from about 5,000 MPa to about 18,000 MPa, and in some embodiments from about 6,000 MPa to about 15,000 MPa. Flexural properties may be determined at 23° C. according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). Molded parts may also exhibit a flexural strength of from about 20 to about 500 MPa, in some embodiments from about 50 to about 400 MPa, and in some embodiments from about 80 to about 350 MPa, and / or a flexural modulus of from about 4,000 MPa to about 20,000 MPa, in some embodiments from about 5,000 MPa to about 18,000 MPa, and in some embodiments from about 6,000 MPa to about 15,000 MPa. Flexural properties may be determined at 23° C. according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). The part may exhibit a deflection temperature under load (DTUL) of about 180° C. or greater, and in some embodiments, from about 190° C. to about 280° C., as measured at a specified load of 1.8 MPa according to ASTM D648-07 (technically equivalent to ISO Test No. 75-2:2013). The part may also have a Rockwell hardness of about 25 or greater, and in some embodiments, from about 30 or greater, and in some embodiments, from about 35 to about 80, as measured according to ASTM D785-08 (Scale M).
[0009]
[0012] Additionally, the compositions can also exhibit excellent antistatic behavior, especially when antistatic fillers are included in the polymer composition as discussed above. The composition may be characterized by a relatively low surface and / or volume resistivity as determined according to IEC-60093. For example, the composition may have a resistivity of about 1×10 15 Ω or less, in some embodiments about 1×10 14 Ω or less, in some embodiments about 1×10 10 Ω ~ approx. 9×10 13 Ω, in some embodiments, about 1×10 11 ~Approx. 1×10 13 The molded part can also exhibit a surface resistivity of about 1×10 15 Ω·m or less, in some embodiments about 1×10 9 Ω m ~ approx. 9×10 14 Ω·m, in some embodiments, about 1×10 10 ~Approx. 5×10 14 Of course, such antistatic behavior is by no means essential. For example, in some embodiments, the composition may exhibit a volume resistivity of about 1×10 15 Ω or more, in some embodiments about 1×10 16 Ω or more, in some embodiments about 1×10 17 Ω ~ approx. 9×10 30 Ω, in some embodiments, about 1×10 18 ~Approx. 1×10 26 It can exhibit a relatively high surface resistivity, such as Ω.
[0010]
[0013] Various embodiments of the invention will now be described in more detail. I. Polymer Composition: A. Aromatic polymers:
[0014] The aromatic polymer typically comprises about 20% to about 70% by weight of the polymer composition, in some embodiments about 30% to about 65% by weight, and in some embodiments about 40% to about 60% by weight. Aromatic polymers are generally considered to be "high performance" polymers having relatively high glass transition temperatures and / or high melting points depending on the specific properties of the polymer. Thus, such high performance polymers can impart a significant degree of heat resistance to the resulting polymer composition. For example, the aromatic polymer may have a glass transition temperature of about 100°C or higher, in some embodiments about 120°C or higher, in some embodiments about 140°C to about 350°C, and in some embodiments about 150°C to about 320°C. The aromatic polymer may also have a melting point of about 200°C or higher, in some embodiments about 220°C to about 400°C, and in some embodiments about 240°C to about 380°C. Glass transition temperatures and melting points may be determined using differential scanning calorimetry (DSC) as is well known in the art, for example by ISO Test Nos. 11357-2:2013 (glass transition temperature) and 11357-3:2011 (melting point).
[0011]
[0015] The aromatic polymer may be substantially amorphous, semi-crystalline, or crystalline. An example of a suitable semi-crystalline aromatic polymer is, for example, an aromatic polyamide. Particularly suitable aromatic polyamides have a relatively high melting point, for example, about 200°C or higher, in some embodiments, about 220°C or higher, in some embodiments, about 240°C to about 320°C, as determined using differential scanning calorimetry according to ISO Test No. 11357. Additionally, the glass transition temperature of aromatic polyamides is generally about 110°C to about 160°C.
[0012]
[0016] Aromatic polyamides typically contain repeat units linked by amide bonds (NH-CO) and are synthesized by polycondensation of dicarboxylic acids (e.g., aromatic dicarboxylic acids), diamines (e.g., aliphatic diamines), and the like. For example, aromatic polyamides may contain aromatic repeat units derived from aromatic dicarboxylic acids, such as terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,4-phenylenedioxy-diacetic acid, 1,3-phenylenedioxy-diacetic acid, diphenic acid, 4,4'-oxydibenzoic acid, diphenylmethane-4,4'-dicarboxylic acid, diphenylsulfone-4,4'-dicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and the like, as well as combinations thereof. Terephthalic acid is particularly preferred. Of course, it should be understood that other types of acid units, such as aliphatic dicarboxylic acid units, polyfunctional carboxylic acid units, and the like, can also be used. The aromatic polyamides may also contain aliphatic repeat units derived from aliphatic diamines, usually having from 4 to 14 carbon atoms. Examples of such diamines include linear aliphatic alkylenediamines, For example, 1,4-tetramethylenediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, etc.; branched aliphatic alkylene diamines, such as 2-methyl-1,5-pentanediamine, 3-methyl-1,5-pentanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 2-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, etc.; and combinations thereof. Particularly preferred are repeating units derived from 1,9-nonanediamine and / or 2-methyl-1,8-octanediamine. Of course, other diamine units such as alicyclic diamines, aromatic diamines, and the like can also be used.
[0013]
[0017] Particularly suitable polyamides include poly(nonamethylene terephthalamide) (PA9T), poly(nonamethylene terephthalamide / nonamethylene decanediamide) (PA9T / 910), poly(nonamethylene terephthalamide / nonamethylene dodecanediamide) (PA9T / 912), poly(nonamethylene terephthalamide / 11-amino undecanediamide (PA9T / 11), poly(nonamethylene Poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA9T / 12), Poly(decamethylene terephthalamide / 11-amino undecane amide) (PA10T / 11), Poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 12), Poly(decamethylene terephthalamide / decamethylene dodecane diamide) (PA10T / 1010), Poly(decamethylene terephthalamide / 12-amino dodecane amide) (PA10T / 1010), Poly(decamethylene terephthalamide / decamethylene dodecane diamide) (PA10T / 1012), poly(decamethylene terephthalamide / tetramethylene hexane diamide) (PA10T / 46), poly(decamethylene terephthalamide / caprolactam) (PA10T / 6), poly(decamethylene terephthalamide / hexamethylene hexane diamide) (PA10T / 66), poly(dodecamethylene terephthalamide / dodecamethylene dodecane diamide) (PA12T / 1212), poly(dodecamethylene terephthalamide / caprolactam) (PA12T / 6), poly(dodecamethylene terephthalamide / hexamethylene hexane diamide) (PA12T / 66), and the like. Further examples of suitable aromatic polyamides are described in U.S. Pat. No. 8,324,307 to Harder et al.
[0014]
[0018] Other suitable semi-crystalline aromatic polymers that can be used in the present invention are polyaryletherketones. Polyaryletherketones are semi-crystalline polymers having relatively high melting points, such as from about 300°C to about 400°C, in some embodiments from about 310°C to about 390°C, and in some embodiments from about 330°C to about 380°C. Also, the glass transition temperature may be from about 110°C to about 200°C. Particularly suitable polyaryletherketones are those that contain primarily phenyl groups in combination with ketone and / or ether groups. Examples of such polymers include polyetheretherketone (PEEK), polyetherketone (PEK), polyetherketoneketone (PEKK), polyetherketoneetherketoneketone (PEKEKK), polyetheretherketoneketone (PEEKK), polyether-diphenyl-ether-ether-diphenyl-ether-phenyl-ketone-phenyl, and the like, as well as blends and copolymers thereof.
[0015]
[0019] As noted above, substantially amorphous polymers without a discernible melting point can also be used in the polymer composition. Suitable amorphous polymers include, for example, polyphenylene oxide (PPO), aromatic polycarbonates, aromatic polyetherimides, and the like. For example, aromatic polycarbonates typically have a glass transition temperature of about 130°C to about 160°C and contain aromatic repeat units derived from one or more aromatic diols. Particularly suitable aromatic diols are bisphenols, such as gem-bisphenols, in which two phenolic groups are bonded to a single carbon atom of a divalent linking group. Examples of such bisphenols include, for example, 4,4'-isopropylidenediphenol (bis Phenol A), 4,4'-ethylidene diphenol, 4,4'-(4-chloro-a-methylbenzylidene)diphenol, 4,4'-cyclohexylidene diphenol, 4,4-(cyclohexylmethylene)diphenol, and the like, as well as combinations thereof. The aromatic diol can be reacted with phosgene. For example, phosgene can be carbonyl chloride having the formula C(O)Cl2. Other routes to the synthesis of aromatic polycarbonates can include the transesterification of aromatic diols (e.g., bisphenols) with diphenyl carbonate.
[0016]
[0020] In addition to the above polymers, crystalline polymers can also be used in the polymer composition. Liquid crystal polymers with high crystallinity that allow for efficient filling of small spaces in the mold are particularly suitable. Liquid crystal polymers are generally classified as "thermotropic" insofar as they have a rod-like structure and can exhibit crystalline behavior in their molten state (e.g., thermotropic nematic state). The polymers have relatively high melting points, such as from about 250°C to about 400°C, in some embodiments from about 280°C to about 390°C, and in some embodiments from about 300°C to about 380°C. Such polymers can be formed from one or more types of repeating units, as known in the art. Liquid crystal polymers can include, for example, one or more aromatic ester repeating units, typically in an amount of from about 60 mol% to about 99.9 mol%, in some embodiments from about 70 mol% to about 99.5 mol%, and in some embodiments from about 80 mol% to about 99 mol% of the polymer. The aromatic ester repeating units are generally represented by the following formula (I):
[0017] [ka]
[0018] (In the formula, Ring B is a substituted or unsubstituted 6-membered aryl group (e.g., 1,4-phenylene or 1,3-phenylene), a substituted or unsubstituted 6-membered aryl group fused to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 2,6-naphthalene), or a substituted or unsubstituted 6-membered aryl group bonded to a substituted or unsubstituted 5- or 6-membered aryl group (e.g., 4,4-biphenylene); Y1 and Y2 are independently O, C(O), NH, C(O)HN, or NHC(O). It can be expressed as:
[0019]
[0021] Typically, at least one of Y1 and Y2 is C(O). Examples of such aromatic ester repeat units include, for example, aromatic dicarboxylic acid repeat units (in formula I, Y1 and Y2 are C(O)), aromatic hydroxycarboxylic acid repeat units (in formula I, Y1 is O and Y2 is C(O)), and various combinations thereof.
[0020]
[0022] For example, terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 4,4'-dicarboxybiphenyl, bis(4-carboxyphenyl)ether, bis(4-carboxyphenyl)butane, bis(4-carboxyphenyl)butane, Aromatic dicarboxylic acid repeat units derived from aromatic dicarboxylic acids such as bis(3-carboxyphenyl)ethane, bis(3-carboxyphenyl)ether, bis(3-carboxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, can be used. Particularly suitable aromatic dicarboxylic acids include, for example, terephthalic acid (TA), isophthalic acid (IA), and 2,6-naphthalenedicarboxylic acid (NDA). When used, repeat units derived from aromatic dicarboxylic acids (e.g., IA, TA, and / or NDA) typically comprise from about 5 mol % to about 60 mol %, in some embodiments from about 10 mol % to about 55 mol %, and in some embodiments, from about 15 mol % to about 50 mol % of the polymer.
[0021]
[0023] Aromatic hydroxycarboxylic acid repeat units derived from aromatic hydroxycarboxylic acids such as 4-hydroxybenzoic acid, 4-hydroxy-4'-biphenylcarboxylic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-5-naphthoic acid, 3-hydroxy-2-naphthoic acid, 2-hydroxy-3-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and the like, as well as alkyl, alkoxy, aryl, and halogen substituted versions thereof, and combinations thereof, can also be used. Particularly suitable aromatic hydroxycarboxylic acids are 4-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA). When used, repeat units derived from hydroxycarboxylic acids (e.g., HBA and / or HNA) typically comprise about 10 mol% to about 85 mol% of the polymer, in some embodiments about 20 mol% to about 80 mol%, and in some embodiments about 25 mol% to about 75%.
[0022]
[0024] Other repeat units can also be used in the polymer. For example, in some embodiments, repeat units derived from aromatic diols such as hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl (or 4,4'-biphenol), 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, bis(4-hydroxyphenyl)ethane, and the like, as well as alkyl, alkoxy, aryl, and halogen-substituted versions thereof, and combinations thereof can be used. Particularly suitable aromatic diols include, for example, hydroquinone (HQ) and 4,4'-biphenol (BP). When used, repeat units derived from aromatic diols (e.g., HQ and / or BP) typically constitute about 1 mol % to about 30 mol %, in some embodiments, about 2 mol % to about 25 mol %, and in some embodiments, about 5 mol % to about 20 mol % of the polymer. Repeat units such as those derived from aromatic amides (e.g., acetaminophen (APAP)) and / or aromatic amines (e.g., 4-aminophenol (AP), 3-aminophenol, 1,4-phenylenediamine, 1,3-phenylenediamine, etc.) can also be used. When used, repeat units derived from aromatic amides (e.g., APAP) and / or aromatic amines (e.g., AP) typically comprise from about 0.1 mol % to about 20 mol %, in some embodiments from about 0.5 mol % to about 15 mol %, and in some embodiments from about 1 mol % to about 10 mol % of the polymer. It should also be understood that various other monomeric repeat units can be incorporated into the polymer. For example, in some embodiments, the polymer can include one or more repeat units derived from non-aromatic monomers such as aliphatic or alicyclic hydroxycarboxylic acids, dicarboxylic acids, diols, amides, amines, and the like. Of course, in other embodiments, the polymer can be "fully aromatic" in that it does not include repeat units derived from non-aromatic (e.g., aliphatic or alicyclic) monomers.
[0023]
[0025] Although not required, the liquid crystal polymer may be a naphthenic hydroxycarboxylic acid and A polymer may be "low naphthenic" so long as it contains a minimum amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids, such as naphthalene-2,6-dicarboxylic acid (NDA), 6-hydroxy-2-naphthoic acid (HNA), or a combination thereof. That is, the total amount of repeat units derived from naphthenic hydroxycarboxylic acids and / or dicarboxylic acids (e.g., NDA, HNA, or a combination of HNA and NDA) is typically 30 mol% or less of the polymer, in some embodiments about 15 mol% or less, in some embodiments about 10 mol% or less, in some embodiments about 8 mol% or less, and in some embodiments 0 mol% to about 5 mol% (e.g., 0 mol%). Despite the absence of high levels of traditional naphthenic acids, it is believed that the resulting "low naphthenic" polymer can still exhibit good thermal and mechanical properties.
[0024]
[0026] In one particular embodiment, the liquid crystal polymer can be formed from repeat units derived from 4-hydroxybenzoic acid (HBA), and terephthalic acid (TA) and / or isophthalic acid (IA), and various other optional components. The repeat units derived from 4-hydroxybenzoic acid (HBA) can comprise from about 10 mol% to about 80 mol%, in some embodiments from about 30 mol% to about 75 mol%, and in some embodiments from about 45 mol% to about 70% of the polymer. Furthermore, the repeat units derived from terephthalic acid (TA) and / or isophthalic acid (IA) can comprise from about 5 mol% to about 40 mol%, in some embodiments from about 10 mol% to about 35 mol%, and in some embodiments from about 15 mol% to about 35% of the polymer. Repeat units derived from 4,4'-biphenol (BP) and / or hydroquinone (HQ) can also be used in amounts of about 1 mol% to about 30 mol%, in some embodiments about 2 mol% to about 25 mol%, and in some embodiments about 5 mol% to about 20% of the polymer. Other possible repeat units include those derived from 6-hydroxy-2-naphthoic acid (HNA), 2,6-naphthalenedicarboxylic acid (NDA), and / or acetaminophen (APAP). For example, in some embodiments, repeat units derived from HNA, NDA, and / or APAP, if used, can each constitute about 1 mol% to about 35 mol%, in some embodiments about 2 mol% to about 30 mol%, and in some embodiments about 3 mol% to about 25 mol%, respectively.
[0025] B. Tribological Formulations:
[0027] The tribological formulation may also be used in the polymeric composition, typically in an amount of from about 1 to about 30 parts, in some embodiments from about 2 to about 15 parts, and in some embodiments from about 4 to about 12 parts per 100 parts of the aromatic polymer(s) used in the polymeric composition. For example, the tribological formulation may comprise from about 1% to about 30% by weight, in some embodiments from about 2% to about 25% by weight, and in some embodiments from about 4% to about 10% by weight of the polymeric composition.
[0026]
[0028] Tribological formulations generally include a siloxane polymer, which also serves to improve internal lubricity and enhance the wear and friction properties of the composition in contact with another surface. Such siloxane polymers typically comprise from about 0.1 to about 20 parts, in some embodiments from about 0.4 to about 10 parts, and in some embodiments from about 0.5 to about 5 parts per 100 parts of the aromatic polymer or polymers used in the composition. In general, any of a variety of siloxane polymers can be used in the tribological formulation. Siloxane polymers can include, for example, a siloxane polymer having, in the backbone, a structure of the formula: R r SiO (4-r / 2) (In the formula, R is independently hydrogen or a substituted or unsubstituted hydrocarbon group; r is 0, 1, 2 or 3. The present invention may include any polymer, copolymer, or oligomer that includes siloxane units having the formula: do.
[0027]
[0029] Some examples of suitable groups R include, for example, optionally substituted alkyl, aryl, alkylaryl, alkenyl, or alkynyl, or cycloalkyl groups, which may be interrupted by heteroatoms, i.e., may contain one or more heteroatoms in the carbon chain or ring. Suitable alkyl groups include, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and tert-pentyl groups, hexyl groups (e.g., n-hexyl), heptyl groups (e.g., n-heptyl), octyl groups (e.g., n-octyl), isooctyl groups (e.g., 2,2,4-trimethylpentyl), nonyl groups (e.g., n-nonyl), decyl groups (e.g., n-decyl), dodecyl groups (e.g., n-dodecyl), octadecyl groups (e.g., n-octadecyl), and the like. Further, suitable cycloalkyl groups include cyclopentyl, cyclohexyl, cycloheptyl, methylcyclohexyl, etc.; suitable aryl groups include phenyl, biphenyl, naphthyl, anthryl, and phenanthryl; suitable alkylaryl groups include o-, m-, or p-tolyl, xylyl, ethylphenyl, etc.; suitable alkenyl or alkynyl groups include vinyl, 1-propenyl, 1-butenyl, 1-pentenyl, 5-hexenyl, butadienyl, hexadienyl, cyclopentenyl, cyclopentadienyl, cyclohexenyl, ethynyl, propargyl, 1-propynyl, etc. Examples of substituted hydrocarbon groups are halogenated alkyl groups (e.g., 3-chloropropyl, 3,3,3-trifluoropropyl, and perfluorohexylethyl), and halogenated aryl groups (e.g., p-chlorophenyl, and p-chlorobenzyl). In one particular embodiment, the siloxane polymer comprises alkyl groups (e.g., methyl groups) attached to at least 70 mol % of the Si atoms, and optionally vinyl and / or phenyl groups attached to 0.001-30 mol % of the Si atoms. The siloxane polymer also preferably consists primarily of diorganosiloxane units.The end groups of the polyorganosiloxane may be trialkylsiloxy groups, especially trimethylsiloxy groups, or dimethylvinylsiloxy groups. However, one or more of these alkyl groups may be substituted with hydroxy or alkoxy groups, such as methoxy or ethoxy groups. Particularly suitable examples of siloxane polymers include, for example, dimethylpolysiloxane, phenylmethylpolysiloxane, vinylmethylpolysiloxane, and trifluoropropylpolysiloxane.
[0028]
[0030] The siloxane polymers may also contain, on at least a portion of the siloxane monomer units of the polymer, vinyl groups, hydroxyl groups, hydrides, isocyanate groups, epoxy groups, acid groups, halogen atoms, alkoxy groups (e.g., methoxy, ethoxy, and propoxy), acyloxy groups (e.g., acetoxy, and octanoyloxy), ketoximate groups (e.g., dimethylketoxime, methylketoxime, and methylethylketoxime), amino groups (e.g., dimethylamino, diethylamino, and butylamino), aryl groups (e.g., aryloxy ... The aryloxy groups may contain reactive functional groups such as one or more of amide groups (e.g., N-methylacetamide, and N-ethylacetamide), acid amide groups, amino-oxy groups, mercapto groups, alkenyloxy groups (e.g., vinyloxy, isopropenyloxy, and 1-ethyl-2-methylvinyloxy), alkoxyalkoxy groups (e.g., methoxyethoxy, ethoxyethoxy, and methoxypropoxy), aminooxy groups (e.g., dimethylaminooxy, and diethylaminooxy), mercapto groups, and the like.
[0029]
[0031] Regardless of its particular structure, the siloxane polymer typically has a relatively high molecular weight, which reduces its tendency to migrate or diffuse to the surface of the polymer composition, thus further minimizing the possibility of phase separation. For example, the siloxane polymer typically has a molecular weight of at least about 100,000 grams / mole, and in some embodiments, at least about 200,000 grams / mole. The siloxane polymer may also have a relatively high kinematic viscosity, such as greater than or equal to about 10,000 centistokes, in some embodiments greater than or equal to about 30,000 centistokes, and in some embodiments, from about 50,000 to about 500,000 centistokes.
[0030]
[0032] If desired, silica particles (e.g., fumed silica) can also be used in combination with the siloxane polymer to help improve its ability to disperse in the composition. Such silica particles can have, for example, a particle size of about 5 nanometers to about 50 nanometers, a particle size of about 50 square meters per gram (m 2 / g) ~ approx. 600m 2 / g surface area, and / or approximately 160 kilograms per cubic meter (kg / m 3 ) ~ approx. 190kg / m 3 The silica particles may have a density of about 100 to about 100 parts by weight, and in some embodiments about 20 to about 60 parts, based on 100 parts by weight of the siloxane polymer. In one embodiment, the silica particles can be mixed with the siloxane polymer before the mixture is added to the polymer composition. For example, a mixture comprising ultra-high molecular weight polydimethylsiloxane and fumed silica can be included in the polymer composition. Such a preformed mixture is available as Genioplast® Pellets S from Wacker Chemie, AG. can.
[0031]
[0033] The tribological formulation may also include other ingredients that may help the resulting polymeric composition achieve a good combination of low friction and good wear resistance. For example, in one embodiment, the tribological formulation may use a fluorinated additive in combination with the siloxane polymer. Without intending to be limited by theory, it is believed that the fluorinated additive may improve the processability of the composition, such as by providing better mold filling, internal lubrication, mold release, among others. When used, the weight ratio of the fluorinated additive to the siloxane polymer is typically about 0.5 to about 12, in some embodiments about 0.8 to about 10, and in some embodiments about 1 to about 6. For example, the fluorinated additive may comprise about 0.1 to about 20 parts, in some embodiments about 0.5 to about 15 parts, and in some embodiments about 1 to about 10 parts per 100 parts of the aromatic polymer(s) used in the composition.
[0032]
[0034] In certain embodiments, the fluorinated additive may include a fluoropolymer comprising a hydrocarbon backbone polymer in which some or all of the hydrogen atoms are replaced with fluorine atoms. The backbone polymer may be polyolefinic and may be formed from fluorine-substituted unsaturated olefin monomers. The fluoropolymer may be a homopolymer of such fluorine-substituted monomers, or a copolymer of fluorine-substituted monomers or a mixture of fluorine-substituted and non-fluorine-substituted monomers. In addition to fluorine atoms, the fluoropolymer may be substituted with other halogen atoms, such as chlorine and bromine atoms. Representative monomers suitable for forming fluoropolymers for use in the present invention are tetrafluoroethylene, vinylidene fluoride, hexafluoropropylene, chlorotrifluoroethylene, perfluoroethyl vinyl ether, perfluoromethyl vinyl ether, perfluoropropyl vinyl ether, and the like, and mixtures thereof. Specific examples of suitable fluoropolymers include polytetrafluoroethylene, perfluoroalkyl vinyl ether, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether), fluorinated ethylene-propylene copolymers, ethylene-tetrafluoroethylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, and the like, and mixtures thereof.
[0033]
[0035] The fluorinated additive may include only the fluoropolymer, or may include other components, such as those that aid in its ability to disperse uniformly within the polymer composition. For example, in one embodiment, the fluorinated additive can include a fluoropolymer in combination with a plurality of substrate particles. In such an embodiment, for example, the fluoropolymer can be coated onto the substrate particles. Talc (Mg3SiO4O 10 (OH)2), halloysite (Al2Si2O5(OH)4), kaolinite (Al2Si2O5(OH)4), illite ((K,H3O)(Al,Mg,Fe)2(Si,Al)4O 10 [(OH)2,(H2O)]), Montmorillonite (Na,Ca)0.33 (Al,Mg)2Si4O 10 (OH)2·nH2O), vermiculite ((MgFe,Al)3(Al,Si)4O 10 (OH)2·4H2O), palygorskite ((Mg,Al)2Si4O 10 (OH)·4(H2O)), pyrophyllite (Al2Si4O 10 Particularly suitable for this purpose are silicate particles such as moscovite (KA12(AlSi3)O4), calcium silicate, aluminum silicate, mica, diatomaceous earth, wollastonite, and the like. For example, mica may be a particularly suitable mineral for use in the present invention. There are several chemically distinct mica species with significant differences in their geological existence, but all have substantially the same crystal structure. As used herein, the term "mica" refers to moscovite (KA12(AlSi3)O4), calcium silicate, aluminum silicate, mica, diatomaceous earth, wollastonite, and the like. 10 (OH)2), Biotite (K(Mg,Fe)3(AlSi3)O 10 (OH)2), phlogopite (KMg3(AlSi3)O 10 (OH)2), lepidolite (K(Li,Al) 2~3 (AlSi3)O 10 (OH)2), gluconite (K,Na)(Al,Mg,Fe)2(Si,Al)4O 10 (OH)2), and the like, as well as combinations thereof, are intended to encompass generically any of these species. The substrate particles may have an average particle size of from about 5 to about 50 micrometers, and in some embodiments, from about 10 to 20 micrometers. If desired, the substrate particles may be in the shape of platelet-like particles, in that the ratio of their major axis to their length is 2 or greater.
[0034] C. Other Optional Ingredients: i. Inorganic filler:
[0036] If desired, inorganic fillers can be used to improve certain properties of the polymer composition. For example, the inventors have found that by using inorganic fillers having certain hardness values, the mechanical strength, adhesive strength, and surface smoothness of parts containing the composition can be improved. The resulting polymer composition can also achieve less delamination of the polymer skin layer, making it particularly suitable for very small parts. The inorganic fillers can be used in the polymer composition in an amount of about 10 to about 95 parts, in some embodiments about 20 to about 90 parts, and in some embodiments about 50 to about 85 parts, by weight, per 100 parts of the aromatic polymer(s) used in the polymer composition. For example, the inorganic fillers can comprise about 10% to about 70% by weight, in some embodiments about 20% to about 60% by weight, and in some embodiments about 30% to about 60% by weight of the polymer composition.
[0035]
[0037] The nature of the inorganic filler can vary, such as particles, fibers, etc. For example, in some embodiments, inorganic filler particles having a particular hardness value can be used to help improve the surface properties of the composition. For example, the hardness value can be about 2.5 or more, in some embodiments about 3.0 or more, in some embodiments about 3.0 to about 11.0, in some embodiments about 3.5 to about 11.0, and in some embodiments about 4.5 to about 6.5, based on the Mohs hardness scale. Examples of such particles include carbonates, such as calcium carbonate (CaCO3; Mohs hardness of 3.0) or copper hydroxide carbonate (Cu2CO3(OH)2; Mohs hardness of 4.0); fluorides, such as calcium fluoride (CaFI2; Mohs hardness of 4.0); phosphates, such as calcium pyrophosphate (Ca2P2O7; Mohs hardness of 5.0), anhydrous dicalcium phosphate (CaHPO4; Mohs hardness of 3.5), or hydrated aluminum phosphate (AlPO4·2H2O; Mohs hardness of 4.5); silica (SiO2; Mohs hardness of 6.0), potassium aluminum silicate (KAlSi3O8; Mohs hardness of 6), or copper silicate (CuSiO3·H2O4; Mohs hardness of 4.0); 0; borates such as calcium hydroxide borosilicate (Ca2B5SiO9(OH)5; Mohs hardness of 3.5); alumina (AlO2; Mohs hardness of 10.0); sulfates such as calcium sulfate (CaSO4; Mohs hardness of 3.5) or barium sulfate (BaSO4; Mohs hardness of 3-3.5), as well as combinations thereof. When used, inorganic particles are typically sized using laser diffraction methods (e.g., Horiba LA-960 particle size analyzer) according to, for example, ISO-13320:2009. The filler inorganic particles may have a median size (e.g., diameter) of about 0.1 to about 35 micrometers, in some embodiments about 2 to about 20 micrometers, in some embodiments about 3 to about 15 micrometers, and in some embodiments about 7 to about 12 micrometers, as determined using a fabric analyzer. The filler inorganic particles may also have a narrow size distribution, i.e., at least about 70% by volume of the particles, in some embodiments at least about 80% by volume of the particles, and in some embodiments at least about 90% by volume of the particles may have a size within the above ranges.
[0036]
[0038] The inorganic filler may also be a fiber derived from a material having the desired hardness value. Particularly suitable fibers for this purpose include those derived from minerals such as silicates, e.g., neosilicates, sorosilicates, inosilicates (e.g., calcium inosilicates such as wollastonite; calcium magnesium inosilicates such as tremolite; calcium magnesium iron inosilicates such as actinolite; magnesium iron inosilicates such as anthophyllite; etc.), phyllosilicates (e.g., aluminum phyllosilicates such as palygorskite), tectosilicates, etc.; sulfates such as calcium sulfate (e.g., dehydrated or anhydrous gypsum); mineral wool (e.g., rock wool or slag wool); and the like. NYGLOS® from Nyco Minerals ( For example, NYGLOS® 4W or NYGLOS® 8 are commercially available. Particularly preferred are fibers derived from inosilicates such as wollastonite (Mohs hardness of 4.5 to 5.0). When used, mineral fibers may be characterized using laser diffraction techniques (e.g., using a Horiba LA-960 particle size distribution analyzer) in accordance with ISO-13320:2009. The mineral fibers may have a median width (e.g., diameter) of about 0.1 to about 35 micrometers, in some embodiments, about 2 to about 20 micrometers, in some embodiments, about 3 to about 15 micrometers, and in some embodiments, about 7 to about 12 micrometers. The mineral fibers may also have a narrow size distribution. That is, at least about 70% by volume of the fibers, in some embodiments, at least about 80% by volume of the fibers, and in some embodiments, at least about 90% by volume of the fibers may have a size within the above range. The mineral fibers may also have an aspect ratio of about 1 to about 50, in some embodiments, about 2 to about 20, and in some embodiments, about 4 to about 15. The volume average length of such mineral fibers may be, for example, in the range of about 1 to about 200 micrometers, in some embodiments, about 2 to about 150 micrometers, in some embodiments, about 5 to about 100 micrometers, and in some embodiments, about 10 to about 50 micrometers.
[0037] ii. Impact Modifiers:
[0039] If desired, impact modifiers may also be used in the polymer composition to help improve the impact strength and flexibility of the polymer composition. In fact, the inventors have found that impact modifiers can actually make the surface of a molded part smoother, minimizing the possibility that a skin layer will peel off therefrom during use. When used, the impact modifiers typically comprise from about 0.1 to about 20 parts, in some embodiments from about 0.2 to about 10 parts, and in some embodiments from about 0.5 to about 5 parts, by weight per 100 parts of the aromatic polymer(s) used in the polymer composition. For example, the impact modifiers may comprise from about 0.1% to about 10% by weight, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments from about 0.5% to about 4% by weight of the polymer composition. It may comprise a percentage by weight.
[0038]
[0040] One particularly suitable type of impact modifier can include, for example, olefin copolymers that are "epoxy-functionalized" in that they contain, on average, two or more epoxy functional groups per molecule. The copolymers generally include olefin monomer units derived from one or more α-olefins. Examples of such monomers include, for example, linear and / or branched α-olefins having from 2 to 20 carbon atoms, usually from 2 to 8 carbon atoms. Specific examples include ethylene, propylene, 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene with one or more methyl, ethyl, or propyl substituents; 1-hexene with one or more methyl, ethyl, or propyl substituents; 1-heptene with one or more methyl, ethyl, or propyl substituents; 1-octene with one or more methyl, ethyl, or propyl substituents; 1-nonene with one or more methyl, ethyl, or propyl substituents; ethyl, methyl, or dimethyl-substituted 1-decene; 1-dodecene; and styrene. Particularly desirable α-olefin monomers are ethylene and propylene. The copolymer may also include epoxy-functional monomer units. One example of such units is an epoxy-functional (meth)acrylic monomer component. As used herein, the term "(meth)acrylic" includes acrylic and methacrylic monomers, as well as salts or esters thereof, such as acrylate and methacrylate monomers. For example, suitable epoxy-functional (meth)acrylic monomers can include, but are not limited to, those containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate. Other suitable epoxy-functional monomers include allyl glycidyl ether, glycidyl ethacrylate, and glycidyl itaconate. Other suitable monomers can also be used. It may also be used to help achieve the desired molecular weight.
[0039]
[0041] Of course, the copolymer may contain other monomer units known in the art. For example, other suitable monomers may include non-epoxy functional (meth)acrylic monomers. Examples of such (meth)acrylic monomers include methyl acrylate, ethyl acrylate, n-propyl acrylate, i-propyl acrylate, n-butyl acrylate, s-butyl acrylate, i-butyl acrylate, t-butyl acrylate, n-amyl acrylate, i-amyl acrylate, isobornyl acrylate, n-hexyl acrylate, 2-ethylbutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, methylcyclohexyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl ... methacrylate, 2-hydroxyethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, i-propyl methacrylate, i-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, i-amyl methacrylate, s-butyl methacrylate, t-butyl methacrylate, 2-ethylbutyl methacrylate, methylcyclohexyl methacrylate, cinnamyl methacrylate, crotyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, 2-ethoxyethyl methacrylate, isobornyl methacrylic acid, and the like, and combinations thereof. For example, in one particular embodiment, the copolymer may be a terpolymer formed from an epoxy-functional (meth)acrylic monomer component, an α-olefin monomer component, and a non-epoxy-functional (meth)acrylic monomer component. The copolymer may, for example, have the following structure:
[0040] [ka]
[0041] (wherein x, y, and z are 1 or greater) The copolymer may be poly(ethylene-co-butyl acrylate-co-glycidyl methacrylate) having the formula:
[0042]
[0042] The relative proportions of the one or more monomeric components can be selected to achieve a balance between epoxy reactivity and melt flow rate. More specifically, a high epoxy monomer content can provide good reactivity with the matrix polymer, but an excessively high content can reduce the melt flow rate to such an extent that the copolymer adversely affects the melt strength of the polymer blend. Thus, in most embodiments, the one or more epoxy-functional (meth)acrylic monomers comprise from about 1% to about 20% by weight of the copolymer, in some embodiments from about 2% to about 15% by weight, and in some embodiments, from about 3% to about 10% by weight. Also, the one or more α-olefin monomers can comprise from about 55% to about 95% by weight, in some embodiments from about 60% to about 90% by weight, and in some embodiments, from about 65% to about 85% by weight of the copolymer. If used, other monomeric components (e.g., non-epoxy functional (meth)acrylic monomers) may comprise from about 5% to about 35% by weight of the copolymer, in some embodiments from about 8% to about 30% by weight, and in some embodiments, from about 10% to about 25% by weight. The resulting melt flow rates are typically from about 1 to about 30 grams per 10 minutes (g / 10 min), in some embodiments from about 2 to about 20 g / 10 min, and in some embodiments from about 3 to about 15 g / 10 min, as determined according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190° C.
[0043] One example of a suitable epoxy-functionalized copolymer that can be used in the present invention is commercially available from Arkema under the name LOTADER® AX8840. LOTADER® AX8840 has, for example, a melt flow rate of 5 g / 10 min and a glycidyl methacrylate monomer content of 8 wt. %. Another suitable copolymer is available from DuPont under the name ELVALOY It is commercially available under the name PTW®, which is a copolymer of ethylene, butyl acrylate, and and glycidyl methacrylate terpolymer having a melt flow rate of 12 g / 10 min and a glycidyl methacrylate monomer content of 4% to 5% by weight.
[0044] iii. Antistatic filler: Antistatic fillers may also be used in the polymeric composition to help reduce the tendency to generate static charge during molding operations, shipping, recovery, assembly, and the like. When used, such fillers typically comprise from about 0.1 to about 20 parts, in some embodiments from about 0.2 to about 10 parts, and in some embodiments from about 0.5 to about 5 parts, by weight per 100 parts of the aromatic polymer(s) used in the polymeric composition. For example, the antistatic filler may comprise from about 0.1% to about 10% by weight, in some embodiments from about 0.2% to about 8% by weight, and in some embodiments from about 0.5% to about 4% by weight of the polymeric composition.
[0045]
[0045] Generally, any of a variety of antistatic fillers can be used in the polymer composition to help improve its antistatic properties. Examples of suitable antistatic fillers can include, for example, metal particles (e.g., aluminum flakes), metal fibers, carbon particles (e.g., graphite, expanded graphite, graphene, carbon black, graphitized carbon black, etc.), carbon nanotubes, carbon fibers, etc. Carbon fibers and carbon particles (e.g., graphite) are particularly suitable. When used, suitable carbon fibers can include pitch-based carbon (e.g., tar pitch), polyacrylonitrile-based carbon, metal-coated carbon, etc. Desirably, the carbon fibers have a high purity in that they have a relatively high carbon content, for example, about 85% by weight or more, in some embodiments about 90% by weight or more, and in some embodiments about 93% by weight or more. For example, the carbon content can be at least about 94% by weight, such as at least about 95% by weight, such as at least about 96% by weight, such as at least about 97% by weight, or even at least about 98% by weight. The carbon purity is generally less than 100% by weight, for example less than about 99% by weight. The density of carbon fibers is usually about 0.5 to about 3.0 g / cm 3 and in some embodiments, from about 1.0 to about 2.5 g / cm 3 and in some embodiments, from about 1.5 to about 2.0 g / cm 3 It is.
[0046] In one embodiment, the carbon fibers are incorporated into the matrix with minimal fiber breakage. The volume average length of the fibers after molding can generally be from about 0.1 mm to about 1 mm, even with fibers having an initial length of about 3 mm. The average length and distribution of the carbon fibers can also be selectively controlled in the final polymer composition to achieve better connections and electrical flow paths within the liquid crystal polymer matrix. The average diameter of the fibers can be from about 0.5 to about 30 micrometers, in some embodiments from about 1 to about 20 micrometers, and in some embodiments from about 3 to about 15 micrometers.
[0047] To improve dispersion within the polymer matrix, the carbon fibers can be at least partially coated with a sizing agent that increases the compatibility of the carbon fibers with the liquid crystal polymer. The sizing agent can be stable and not thermally decomposed at the temperature at which the liquid crystal polymer is molded. In one embodiment, the sizing agent can include a polymer, such as an aromatic polymer. For example, the aromatic polymer can have a thermal decomposition temperature greater than about 300° C., such as greater than about 350° C., such as greater than about 400° C. As used herein, the thermal decomposition temperature of a material is the temperature at which the material loses 5% of its mass during thermogravimetric analysis, as determined according to ASTM test E-1131 (or ISO test 11358). The sizing agent can also have a relatively high glass transition temperature. For example, the glass transition temperature of the sizing agent can be greater than about 300° C., such as greater than about 350° C., such as greater than about 400° C. Specific examples of sizing agents include polyimide polymers, aromatic polyester polymers, such as fully aromatic polyester polymers, and high temperature epoxy polymers. In one embodiment, the sizing agent can include a liquid crystal polymer. The sizing agent can be present on the fiber in an amount of at least about 0.1% by weight, such as at least 0.2% by weight, such as at least about 0.1% by weight. The sizing agent is generally present in an amount of less than about 5% by weight, such as less than about 3% by weight.
[0048]
[0048] Another suitable antistatic filler is ionic liquid. One advantage of such materials is that, in addition to being antistatic, ionic liquids can also exist in liquid form during melt processing, which allows them to be blended more uniformly into the polymer matrix. This improves electrical conductivity, thereby increasing the ability of the composition to quickly dissipate static charge from its surface.
[0049] Ionic liquids are generally salts that have a melting point low enough to be in liquid form when melt processed with the liquid crystalline polymer. For example, the melting point of the ionic liquid may be about 400° C. or less, in some embodiments about 350° C. or less, in some embodiments about 1° C. to about 100° C., and in some embodiments about 5° C. to about 50° C. The salt comprises a cationic species and a counterion. The cationic species includes compounds having at least one heteroatom (e.g., nitrogen or phosphorus) as the "cation center". Examples of such heteroatom compounds include those having the following structures:
[0050] [ka]
[0051] (In the formula, R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , and R 8 are independently hydrogen; substituted or unsubstituted C1-C 10 Alkyl groups (e.g., methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, etc.); substituted or unsubstituted C3-C 14 Cycloalkyl groups (e.g., adamantyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclooctyl, cyclohexenyl, etc.); substituted or unsubstituted C1-C 10 Alkenyl groups (e.g., ethylene, propylene, 2-methylpropylene, pentylene, etc.); substituted or unsubstituted C2-C 10 Alkynyl groups (e.g., ethynyl, propynyl, etc.); substituted or unsubstituted C1-C 10 Alkoxy groups (e.g. For example, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, t-butoxy, sec-butoxy, n-pentoxy, etc.; substituted or unsubstituted acyloxy groups (for example, methacryloxy, methacryloxyethyl, etc.); substituted or unsubstituted aryl groups (for example, phenyl); substituted or unsubstituted heteroaryl groups (for example, pyridyl, furanyl, thienyl, thiazolyl, isothiazolyl, triazolyl, imidazolyl, isoxazolyl, pyrrolyl, pyrazolyl, pyridazinyl, pyrimidinyl, quinolyl, etc.); and the like. For example, in one particular embodiment, the cationic species is a quaternary onium having the structure: + R 1 R 2 R 3 R 4 (In the formula, R 1 , R 2 , and / or R 3 are independently C1-C6 alkyl (e.g., methyl, ethyl, butyl, etc.), and R 4 may be an ammonium compound having a hydrogen or a C1-C4 alkyl group (e.g., methyl or ethyl). For example, the cationic component may be tributylmethylammonium (R 1 , R 2 , and R 3 is butyl, and R 4 is methyl).
[0052] Suitable counterions for the cationic species include, for example, halogens (e.g., chlorine, bromine, iodine, etc.); sulfates or sulfonates (e.g., methyl sulfate, ethyl sulfate, butyl sulfate, hexyl sulfate, octyl sulfate, hydrogen sulfate, methanesulfonate, dodecylbenzenesulfonate, dodecyl sulfate, trifluoromethanesulfonate, heptadecafluorooctanesulfonate, sodium dodecylethoxysulfate, etc.); sulfosuccinates; amides (e.g., dicyanamide); imides (e.g., bis(pentafluoroethyl-sulfonyl)imide, bis(trifluoromethylsulfonyl)imide, bis(trifluoromethyl)imide, etc.); borates (e.g., the tetrafluoroborate, tetracyanoborate, bis[oxalato]borate, bis[salicylate]borate, etc.); phosphate or phosphinate (e.g., hexafluorophosphate, diethylphosphate, bis(pentafluoroethyl)phosphinate, tris(pentafluoroethyl)trifluorophosphate, tris(nonafluorobutyl)trifluorophosphate, etc.); antimonate (e.g., hexafluoroantimonate); aluminate (e.g., tetrachloroaluminate); fatty acid carboxylate (e.g., oleate, isostearate, pentadecafluorooctanoate, etc.); cyanate; acetate; etc., and combinations of any of the above. To help improve compatibility with the liquid crystal polymer, it may be desirable to select a substantially generally hydrophobic counterion, such as imide, fatty acid carboxylate, etc. Particularly suitable hydrophobic counterions include, for example, bis(pentafluoroethylsulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(trifluoromethyl)imide.
[0053] iv. Other additives: A wide range of further additives can also be included in the polymer composition, such as lubricants, thermally conductive fillers, pigments, antioxidants, stabilizers, surfactants, waxes, flame retardants, anti-sag agents, and other materials added to improve properties and processability. For example, lubricants that can withstand the processing conditions of the liquid crystal polymer without substantial decomposition can be used in the polymer composition. Examples of such lubricants include fatty acid esters, their salts, esters, fatty acid amides, organic phosphate esters, and hydrocarbon waxes of the type commonly used as lubricants in the processing of engineering plastic materials, and mixtures thereof. Suitable fatty acids usually have a backbone carbon chain of about 12 to about 60 carbon atoms, such as myristic acid, palmitic acid, stearic acid, arachidic acid, montanic acid, octadecinic acid, parinric acid, and the like. Suitable esters include fatty acid esters, fatty alcohol esters, wax esters, glycerol esters, glycol esters, and complex esters. Fatty acid amides include fatty acid primary amides, fatty acid secondary amides, methylene and ethylene esters. Suitable lubricants include ethylene bisamides, and alkanolamides, such as palmitic acid amide, stearic acid amide, oleic acid amide, N,N'-ethylene bisstearamide, and the like. Also suitable are metal salts of fatty acids, such as calcium stearate, zinc stearate, magnesium stearate, and the like; and hydrocarbon waxes, such as paraffin wax, polyolefin and oxidized polyolefin waxes, and microcrystalline waxes. Particularly suitable lubricants are stearic acids, salts, or amides, such as pentaerythritol tetrastearate, calcium stearate, or N,N'-ethylene bisstearamide. When used, the lubricant or lubricants typically comprise from about 0.05% to about 1.5% by weight, and in some embodiments, from about 0.1% to about 0.5% by weight (by weight) of the polymer composition.
[0054] Of course, one beneficial feature of the present invention is the ability to achieve good mechanical properties without adversely affecting the dimensional stability of the resulting part. To help ensure that this dimensional stability is maintained, it is generally desirable to leave the polymer composition substantially free of conventional fibrous fillers, such as glass fibers. Thus, if used at all, such fibers will typically comprise no more than about 10% by weight of the polymer composition, in some embodiments no more than about 5% by weight, and in some embodiments from about 0.001% to about 3% by weight.
[0055] II. Formation: The aromatic polymer, tribological formulation, and other optional additives can be melt processed or blended together. These components can be fed separately or in combination to an extruder that includes at least one screw rotatably mounted and housed within a barrel (e.g., a cylindrical barrel) and can define along the length of the screw a feed section and a melt section disposed downstream of the feed section. The extruder can be a single or twin screw extruder. The speed of the screw can be selected to achieve the desired residence time, shear rate, melt processing temperature, and the like. For example, the screw speed can range from about 50 to about 800 revolutions per minute (rpm), in some embodiments from about 70 to about 150 rpm, and in some embodiments from about 80 to about 120 rpm. Also, the apparent shear rate during melt blending can be about 100 s -1 ~about 10,000 seconds -1 , in some embodiments, about 500 seconds -1 ~about 5000 seconds -1 , in some embodiments, about 800 seconds -1 ~about 1200 seconds -1 The apparent shear rate can be in the range of 4Q / πR 3 (where Q is the volumetric flow rate of the polymer melt (m 3 / sec), where R is the radius (m) of the capillary (e.g., extruder die) through which the molten polymer flows.
[0056] The inventors have found that regardless of the particular method by which it is formed, the resulting polymer composition can have excellent thermal properties. For example, the melt viscosity of the polymer composition can be sufficiently low so that it can easily flow into a mold cavity having small dimensions. In one particular embodiment, the polymer composition can be melted at a temperature of 1000 s. -1 The composition may have a melt viscosity of from about 1 to about 200 Pa·s, in some embodiments from about 5 to about 180 Pa·s, in some embodiments from about 10 to about 150 Pa·s, and in some embodiments from about 60 to about 120 Pa·s, measured at a shear rate of from about 1 to about 200 Pa·s. The melt viscosity may be measured at 15° C. above the melting point of the composition (e.g., 350° C.) according to ISO Test No. 11443:2005.
[0057] III. Molded parts:
[0055] A variety of different techniques can be used to form molded parts from the polymeric compositions. Suitable techniques include, for example, injection molding, low pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low pressure gas injection molding, low pressure foam injection molding, gas extrusion compression molding, Examples include foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, and the like. For example, an injection molding system can be used, including a mold into which the polymer composition can be injected. The time inside the injector can be controlled and optimized to prevent the polymer matrix from prematurely solidifying. When the cycle time is reached and the barrel is full for discharge, a piston can be used to inject the composition into the mold cavity. A compression molding system can also be used. Similar to injection molding, molding of the polymer composition into the desired article also takes place in the mold. The composition can be placed in the compression mold using any known technique, for example by picking up by an automated robotic arm. The temperature of the mold can be maintained above the solidification temperature of the polymer matrix for the desired time to allow solidification. The molded article can then be solidified by bringing it below its melting point. The resulting product can be demolded. The cycle time of each molding process can be adjusted to match the polymer matrix, achieve sufficient bonding, and increase the productivity of the overall process.
[0058]
[0056] Due to its high flowability, relatively thin molded parts (e.g., injection molded parts) can be readily formed therefrom. For example, such parts can have a thickness of about 10 millimeters or less, in some embodiments about 5 millimeters or less, and in some embodiments, about 0.2 to about 4 millimeters (e.g., 0.3 or 3 millimeters). In forming injection molded parts, for example, a relatively high "spiral flow length" can be achieved. The term "spiral flow length" generally refers to the length reached by the flow of a composition in a spiral flow passage when injected at a constant injection temperature and pressure through the central gate of a mold in which the spiral flow passage is formed. The spiral flow length can be measured, for example, according to ASTM D3121-09, at a barrel temperature of 230°C, a mold temperature of 40°C to 60°C, and The diameter may be about 15 millimeters or more, in some embodiments about 20 millimeters or more, in some embodiments about 22 millimeters or more, and in some embodiments, from about 25 to about 80 millimeters, measured at a maximum injection pressure of 860 bar.
[0059] The polymeric compositions can also remain dimensionally stable when molded into parts, and therefore exhibit a relatively low degree of warpage. The degree of warpage can be characterized by a low "flatness value" as determined by a test described in more detail below. More specifically, the polymeric compositions can exhibit flatness values of about 1 millimeter or less, in some embodiments about 0.8 millimeters or less, and in some embodiments, about 0.1 to about 0.7 millimeters. The compositions can also maintain such low warpage even after conditioning at high temperatures and humidity levels (e.g., 85° C. and 85% relative humidity) for a significant period of time (e.g., 72 hours). For example, after conditioning at 85° C. / 85% relative humidity for 72 hours, the polymeric compositions can still exhibit flatness values of about 2 millimeters or less, in some embodiments about 1.5 millimeters or less, and in some embodiments, about 0.1 to about 1.2 millimeters.
[0060] A wide variety of types of parts can also be formed from the polymer compositions of the present invention. For example, the polymer compositions can be used in lighting assemblies, battery systems, sensors and electronic components, portable electronic devices such as smart phones, MP3 players, cell phones, computers, televisions, automotive parts, and the like. In one particular embodiment, the polymer compositions can be used in camera modules such as those commonly used in wireless communication devices (e.g., cell phones). For example, the camera module can include a base, a support assembly mounted on the base, a cover mounted on the support assembly, and the like. The base can be about 500 micrometers or less, in some embodiments about 10 to about 450 micrometers, and in some embodiments, about 10 to about 500 micrometers. The support assembly may have a thickness of from about 20 to about 400 micrometers. Further, the support assembly may have a wall thickness of up to about 500 micrometers, in some embodiments, from about 10 to about 450 micrometers, and in some embodiments, from about 20 to about 400 micrometers.
[0061]
[0059] One particularly suitable camera module is shown in Figures 1-2. As shown, the camera module 500 includes a support assembly 504 disposed on a base 506. The base 506 is in turn disposed on an optional main board 508. Due to their relatively thin characteristics, the base 506 and / or the main board 508 are particularly suitable for molding from the polymer composition of the present invention. The support assembly 504 may have any of a variety of configurations known in the art. For example, in one embodiment, the support assembly 504 may include a hollow barrel housing one or more lenses 604, which are disposed on the main board 508 and communicate with an image sensor 602 controlled by a circuit 601. The barrel may have any of a variety of shapes, such as rectangular, cylindrical, etc. In some embodiments, the barrel may be formed from the polymer composition of the present invention and may have a wall thickness within the ranges described above. It should be understood that other components of the camera module may also be formed from the polymer composition of the present invention. For example, as shown, the support assembly 504 can be covered by a cover including, for example, a substrate 510 (e.g., a film) and / or an insulating cap 502. In some embodiments, the substrate 510 and / or the cap 502 can also be formed from the present polymeric compositions. EXAMPLES
[0062] The invention can be better understood with reference to the following examples. Test Method:
[0061] Friction and wear: Using SSP-03 machine, VDA 230-206:2007 (steer The degree of friction generated by the specimen can be characterized by the average dynamic friction coefficient (dimensionless) determined according to the VDA 230-206:2007 (Dynamic Slip Test). The degree of wear of the test specimen can also be determined according to VDA 230-206:2007. More specifically, the polymer product is used to prepare ball-shaped and plate-shaped specimens by an injection molding process. The ball specimens are 0.5 inches in diameter. The plate specimens are obtained from the center of an ISO tensile bar by cutting the two end regions of the tensile bar. The plate specimen is fixed on a specimen holder and the ball specimen is moved in contact with the plate specimen at 150 mm / s and a force of 15 N. After 1000 cycles, the dynamic friction coefficient is obtained. The wear depth is obtained from the ball specimen by measuring the diameter of the worn ball area. Based on the diameter of the worn area, the wear depth of the ball specimen is calculated.
[0063] Melt Viscosity: Melt viscosity (Pa·sec) was measured at 1000 s using a Dynisco LCR 7001 capillary flowmeter in accordance with ISO Test No. 11443:2005. -1 and a temperature 15° C. above the melting point (e.g., 350° C.). The flowmeter orifice (die) had a diameter of 1 mm, a length of 20 mm, an L / D ratio of 20.1, and an entrance angle of 180°. The barrel diameter was 9.55 mm+0.005 mm and the rod length was 233.4 mm.
[0064]
[0063] Melting point: Melting point (Tm) can be determined by differential scanning calorimetry (DSC) as known in the art. Melting point is the differential scanning calorimetry (DSC) peak melting temperature as determined by ISO test No. 11357-2:2013. In the DSC procedure, samples were heated and cooled at 20°C / min as specified in ISO standard 10350 with DSC measurements performed on a TA-Q2000 instrument.
[0065]
[0064] Deflection temperature under load (DTUL): Deflection temperature under load can be determined according to ISO Test No. 75-2:2013 (technically equivalent to ASTM D648-07). More specifically, a test specimen sample having a length of 80 mm, a thickness of 10 mm, and a width of 4 mm can be subjected to a lateral three-point bending test with a prescribed load (maximum outer fiber stress) of 1.8 megapascals. The test specimen can be lowered into a silicone oil bath where the temperature is increased at 2°C / min until it is deflected 0.25 mm (0.32 mm for ISO Test No. 75-2:2013).
[0066] Tensile modulus, tensile stress, and tensile elongation: Tensile properties can be tested according to ISO Test No. 527:2012 (technically equivalent to ASTM D638-14). Modulus and strength measurements can be performed on the same test specimen sample having a length of 80 mm, a thickness of 10 mm, and a width of 4 mm. The test temperature can be 23° C., and the test speed can be 1 or 5 mm / min.
[0067] Flexural modulus and flexural stress: Flexural properties can be tested according to ISO Test No. 178:2010 (technically equivalent to ASTM D790-10). The test can be performed on a support span of 64 mm. The test can be performed on the center section of an uncut ISO-3167 multipurpose bar. The test temperature can be 23° C. and the test speed can be 2 mm / min.
[0068] Unnotched and notched Charpy impact strength: Charpy properties can be tested according to ISO Test No. 179-1:2010 (technically equivalent to ASTM D256-10, Method B). The test can be performed using Type 1 specimen dimensions (80 mm length, 10 mm width, and 4 mm thickness). When testing notched impact strength, the notch can be a Type A notch (0.25 mm base radius). Specimens can be cut from the center of the general purpose bar using a single tooth milling machine. The test temperature can be 23°C.
[0069] Rockwell Hardness: Rockwell hardness is a measure of the indentation resistance of a material and may be determined according to ASTM D785-08 (scale M). The test is performed by first pressing a steel ball indenter into the surface of the material with a small, specified load. The load is then increased to a large, specified load and decreased back to the original small load. Rockwell hardness is a measure of the net increase in indenter depth and is calculated by subtracting 130 from the amount of penetration divided by the scale division.
[0070] Surface / Volume Resistivity: Surface and volume resistivity values are generally determined according to IEC-60093 (equivalent to ASTM D257-07). According to this procedure, a standard test piece (e.g., 1 meter cubed) is placed between two electrodes. A voltage is applied for 60 seconds and the resistance is measured. Surface resistivity is the quotient of the potential gradient (V / m) and the current per unit electrode length (A / m), and generally represents the resistance to leakage current along the surface of an insulating material. Since the four edges of the electrode define a square, the length is reduced in the quotient and the surface resistivity is reported in Ω, although it is common to see the more descriptive unit of Ω / square. Volume resistivity is also determined as the ratio of the potential gradient parallel to the current in the material to the current density. In SI units, volume resistivity is numerically equal to the DC resistance (Ω·m) between the opposing faces of a 1 meter cube of material.
[0071] Weld Line Strength: Weld line strength can be determined by first forming an injection molded compact camera module from a sample of the polymer composition, as is well known in the art. Once formed, the compact camera module can be placed on a sample holder. The module is then welded by a rod moving at a speed of 5.08 millimeters per minute. The weld line of the mold can be subjected to a tensile force. Maximum force at break (kg f ) can be recorded as an estimate of the weld line strength.
[0072] Spiral flow length: The term "spiral flow length" generally refers to the length reached by the flow of a composition in a spiral channel (0.3 mm thick) when injected at a constant injection temperature and pressure through the central gate of a mold in which the spiral channel is formed. The spiral flow length can be determined according to ASTM D3121-09 at a barrel temperature of 230°C, a mold temperature of 40°C to 60°C, and a maximum injection pressure of 860 bar. Cut.
[0073] Flatness Value: The flatness value (warpage) of the LGA connector samples can be measured using an OGP Smartscope Quest 300 optical measurement system. XYZ measurements can be taken across the specimen starting from X and Y values corresponding to 5, 22.5, 50, 57.5, and 75 mm. The Z values can be normalized so that the minimum Z value corresponds to a height of zero. The flatness value is calculated as the average of the 25 normalized Z values.
[0074] Example 1:
[0073] Various proportions of liquid crystal polymer, barium sulfate, impact modifier (Lotader® 8840), tribological formulation, black masterbatch, and antistatic filler were used as shown in Table 1 below. The tribological formulation is a combination of a high molecular weight siloxane polymer (Genioplast® Pellet S) and a fluorinated additive (Thor FPz mica). The black masterbatch contains 80% by weight of liquid crystal polymer and 20% by weight of carbon black. The antistatic filler is an ionic liquid, namely, tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)-imide (FC-4400 from 3M). The liquid crystal polymer (LCP-1) in Samples 1 to 4 is the same as that disclosed in U.S. Patent No. 5,508 to Lee et al. The liquid crystal polymer (LCP-1) in Samples 5-6 is made from HBA, HNA, TA, BP, and APAP as described in U.S. Pat. No. 374, and the liquid crystal polymer (LCP-2) in Samples 5-6 is made from HBA, HNA, and TA. Compounding is performed using an 18 mm single screw extruder. The samples are injection molded into plaques (60 mm x 60 mm) to form parts.
[0075] [Table 1]
[0076]
[0074] Samples 1-3 and 5-6 are also tested for thermal, mechanical and wear properties. The results are shown in Table 2 below.
[0077] [Table 2]
[0078] Example 2:
[0075] Various proportions of liquid crystal polymer, inorganic filler (barium sulfate or mica), impact modifier (Lotader® 8840), tribological formulation, and black paint were used as shown in Table 3 below. From the masterbatches, samples 7 to 12 are formed. The tribological formulations consist of a high molecular weight siloxane polymer (Genioplast® Pellet S) and a fluorinated additive (KT-300MPT The black masterbatch contains 80% by weight of liquid crystal polymer and 20% by weight of carbon black. The liquid crystal polymer (LCP-1) in Samples 10-12 is a combination of HBA, HNA, TA, and FE, as described in U.S. Patent No. 5,508,374 to Lee et al. The liquid crystal polymer (LCP-1) in Samples 7-9 is made from HBA, HNA, and TA. Compounding is carried out using an 18 mm single screw extruder. The samples are injection molded into plaques (60 mm x 60 mm) to form parts.
[0079] [Table 3]
[0080]
[0076] Samples 7-12 were also tested for thermal, mechanical and wear properties, with the results shown in Table 4 below.
[0081] [Table 4]
[0082]
[0077] These and other modifications and variations of the present invention may be implemented by those skilled in the art without departing from the spirit and scope of the present invention. Furthermore, it should be understood that aspects of the various embodiments may be interchanged in whole or in part. Furthermore, those skilled in the art will appreciate that the above description is for illustrative purposes only and is not intended to limit the invention as further described in the appended claims. The claims as filed are set forth below. [Claim 1] 1. A polymer composition comprising: at least one aromatic polymer; and a tribological formulation in an amount of about 1 to about 20 parts by weight per 100 parts by weight of said aromatic polymer, said tribological formulation comprising a fluorinated additive and a siloxane polymer having a weight average molecular weight of about 100,000 grams / mole or greater, and further comprising a weight ratio of said fluorinated additive to said siloxane polymer of about 0.5 to about 12. [Claim 2] 10. The polymer composition of claim 1, wherein the aromatic polymer comprises from about 20% to about 70% by weight of the polymer composition and the tribological formulation comprises from about 1% to about 30% by weight of the polymer composition. [Claim 3] 10. The polymer composition of claim 1, wherein the siloxane polymer is present in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of the aromatic polymer. [Claim 4] The siloxane polymer has in its backbone a structure of the formula: R rSiO (4-r / 2) (wherein R is independently hydrogen or a substituted or unsubstituted hydrocarbon group, and r is 0, 1, 2, or 3). 2. The polymer composition of claim 1, comprising siloxane units having the formula: [Claim 5] 5. The polymer composition of claim 4, wherein the siloxane polymer comprises alkyl groups bonded to at least 70 mol % of the Si atoms. [Claim 6] 10. The polymer composition of claim 1, wherein the siloxane polymer comprises dimethylpolysiloxane, phenylmethylpolysiloxane, vinylmethylpolysiloxane, trifluoropropylpolysiloxane, or a combination thereof. [Claim 7] 10. The polymer composition of claim 1, wherein the siloxane polymer has a kinematic viscosity of about 10,000 centistokes or greater. [Claim 8] 10. The polymer composition of claim 1, wherein the tribological formulation further comprises silica particles. [Claim 9] 10. The polymer composition of claim 1, wherein the fluorinated additive is present in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of the aromatic polymer. [Claim 10] 10. The polymer composition of claim 1, wherein the fluorinated additive comprises a fluoropolymer. [Claim 11] 11. The polymer composition of claim 10, wherein the fluoropolymer comprises polytetrafluoroethylene, perfluoroalkyl vinyl ether, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether), fluorinated ethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, or a combination thereof. [Claim 12] The polymer composition of claim 10, wherein the fluoropolymer is coated on a substrate particle. [Claim 13] The polymer composition of claim 12 , wherein the support particles comprise silicate particles. [Claim 14] 10. The polymer composition of claim 1, further comprising an inorganic filler in an amount of about 10 to about 95 parts by weight per 100 parts by weight of the aromatic polymer. [Claim 15] 15. The polymer composition of claim 14, wherein the inorganic filler comprises particles having a hardness value of about 2.5 or greater on the Mohs hardness scale. [Claim 16] 16. The polymer composition of claim 15, wherein the particles comprise barium sulfate. [Claim 17] 10. The polymer composition of claim 1, further comprising an impact modifier in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of the aromatic polymer. [Claim 18] 20. The polymer composition of claim 17, wherein the impact modifier comprises an epoxy-functionalized olefin copolymer. [Claim 19] 10. The polymer composition of claim 1, further comprising an antistatic filler in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of the aromatic polymer. [Claim 20] 20. The polymer composition of claim 19, wherein the antistatic filler comprises an ionic liquid. [Claim 21] 10. The polymer composition of claim 1, wherein the aromatic polymer has a glass transition temperature of about 100°C or higher and / or a melting point of about 200°C or higher. [Claim 22] 2. The polymer composition of claim 1, wherein the aromatic polymer is a thermotropic liquid crystal polymer. [Claim 23] 23. The polymer composition of claim 22, wherein the liquid crystal polymer comprises repeat units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, hydroquinone, 4,4'-biphenol, acetaminophen, or combinations thereof. [Claim 24] 10. The polymer composition of claim 1, wherein the composition exhibits a dynamic coefficient of friction of about 1.0 or less, as determined according to VDA 230-206:2007. [Claim 25] 10. The polymer composition of claim 1, wherein the composition exhibits an abrasion depth of less than or equal to about 500 micrometers as determined according to VDA 230-206:2007. [Claim 26] 10. The polymer composition of claim 1, wherein the composition exhibits a spiral flow length of about 15 millimeters or greater as determined according to ASTM D3121-09. [Claim 27] A molded part comprising the polymer composition of claim 1. [Claim 28] 27. A camera module comprising the molded part of claim 26. [Claim 29] 1. A camera module comprising a base on which a support assembly is mounted, the base, the support assembly, or both comprising a molded part, the molded part comprising a polymer composition comprising at least one thermotropic liquid crystalline polymer and a tribological formulation, the composition exhibiting a dynamic coefficient of friction of about 1.0 or less as determined in accordance with VDA 230-206:2007. [Claim 30] The composition has a viscosity of about 500 microns as determined according to VDA 230-206:2007. 30. The camera module of claim 29, exhibiting a wear depth of less than one metre. [Claim 31] 30. The camera module of claim 29, wherein the tribological formulation comprises a siloxane polymer having a weight average molecular weight of about 100,000 grams / mole or greater. [Claim 32] 32. The camera module of claim 31, wherein the siloxane polymer has a kinematic viscosity of about 10,000 centistokes or greater. [Claim 33] 30. The camera module of claim 29, wherein the tribological formulation further comprises a fluorinated additive. [Claim 34] 34. The camera module of claim 33, wherein the fluorinated additive comprises a fluoropolymer. [Claim 35] 35. The camera module of claim 34, wherein the fluoropolymer is coated on silicate particles. [Claim 36] 30. The camera module of claim 29, wherein the polymer composition further comprises inorganic filler particles having a hardness value of about 2.5 or greater on the Mohs hardness scale. [Claim 37] 30. The camera module of claim 29, wherein the polymer composition further comprises an impact modifier. [Claim 38] 30. The camera module of claim 29, wherein the polymer composition further comprises an antistatic filler. [Claim 39] 30. The camera module of claim 29, wherein the liquid crystal polymer comprises repeat units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, hydroquinone, 4,4'-biphenol, acetaminophen, or combinations thereof.
Claims
1. 1. A polymer composition comprising at least one thermotropic liquid crystal polymer and a tribological formulation comprising a siloxane polymer having a weight average molecular weight of about 200,000 grams / mole or greater and containing vinyl groups, wherein the siloxane polymer is present in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of the thermotropic liquid crystal polymer.
2. The polymer composition of claim 1, wherein the thermotropic liquid crystalline polymer comprises from about 20% to about 70% by weight of the polymer composition.
3. 10. The polymer composition of claim 1, wherein the siloxane polymer is present in an amount of about 0.4 to about 10 parts by weight per 100 parts by weight of the thermotropic liquid crystalline polymer.
4. The siloxane polymer has in its backbone a structure of the formula: R r SiO (4-r/2) wherein R is independently hydrogen or a substituted or unsubstituted hydrocarbon group, and r is 1, 2, or 3.
2. The polymer composition of claim 1, comprising siloxane units having the formula:
5. The polymer composition of claim 4 , wherein the siloxane polymer comprises alkyl groups bonded to at least 70 mol % of the Si atoms.
6. 10. The polymer composition of claim 1, wherein the siloxane polymer comprises dimethylpolysiloxane, phenylmethylpolysiloxane, vinylmethylpolysiloxane, trifluoropropylpolysiloxane, or a combination thereof.
7. 10. The polymer composition of claim 1, wherein the siloxane polymer has a kinematic viscosity of about 10,000 centistokes or greater.
8. The polymer composition of claim 1 , wherein the polymer composition further comprises silica particles.
9. 10. The polymer composition of claim 1, further comprising a fluorinated additive in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of said thermotropic liquid crystalline polymer.
10. 10. The polymer composition of claim 9, wherein the fluorinated additive comprises a fluoropolymer.
11. 11. The polymer composition of claim 10, wherein the fluoropolymer comprises polytetrafluoroethylene, perfluoroalkyl vinyl ether, poly(tetrafluoroethylene-co-perfluoroalkyl vinyl ether), fluorinated ethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polychlorotrifluoroethylene, or combinations thereof.
12. The polymer composition of claim 10, wherein the fluoropolymer is coated on a substrate particle.
13. The polymer composition of claim 12 , wherein the support particles comprise silicate particles.
14. 10. The polymer composition of claim 1, further comprising an inorganic filler in an amount of about 10 to about 95 parts by weight per 100 parts by weight of said thermotropic liquid crystalline polymer.
15. 15. The polymer composition of claim 14, wherein the inorganic filler comprises particles having a hardness value of about 2.5 or greater on the Mohs hardness scale.
16. 16. The polymer composition of claim 15, wherein the particles comprise barium sulfate.
17. 10. The polymer composition of claim 1, further comprising an impact modifier in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of said thermotropic liquid crystalline polymer.
18. 20. The polymer composition of claim 17, wherein the impact modifier comprises an epoxy-functionalized olefin copolymer.
19. 10. The polymer composition of claim 1, further comprising an antistatic filler in an amount of about 0.1 to about 20 parts by weight per 100 parts by weight of said thermotropic liquid crystalline polymer.
20. 20. The polymer composition of claim 19, wherein the antistatic filler comprises an ionic liquid.
21. 2. The polymer composition of claim 1, wherein the thermotropic liquid crystal polymer comprises repeat units derived from terephthalic acid, isophthalic acid, 2,6-naphthalenedicarboxylic acid, 4-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, hydroquinone, 4,4'-biphenol, acetaminophen, or combinations thereof.
22. 10. The polymer composition of claim 1, wherein the composition exhibits a dynamic coefficient of friction of about 1.0 or less, as determined according to VDA 230-206:2007.
23. 10. The polymer composition of claim 1, wherein the composition exhibits an abrasion depth of less than or equal to about 500 micrometers as determined according to VDA 230-206:2007.
24. 10. The polymer composition of claim 1, wherein the composition exhibits a spiral flow length of greater than or equal to about 15 millimeters as determined according to ASTM D3121-09.
25. 2. The polymer composition of claim 1, comprising the tribological formulation in an amount of about 1 to about 20 parts by weight per 100 parts by weight of the thermotropic liquid crystalline polymer, the tribological formulation comprising a fluorinated additive and the siloxane polymer, and further comprising a weight ratio of the fluorinated additive to the siloxane polymer of about 0.5 to about 12.
Citation Information
Patent Citations
Sealing material with low stress
JP1989163257A
Resin composition
JP1991095259A
Liquid crystal polyester composition
JP1992065455A
Liquid-crystalline resin composition and molding
JP2003306598A
The camera module
JP2017513976A